The Influence of Project-Based Learning Models on the Activities and Learning Outcomes of Vocational Students in Informatics Subjects - Triwahyudi Triwahyudi; Zuwirna Zuwirna; Nurhasan Syah; Ramalis Hakim (STKIP Singkawang, 2025)
This study investigates the effectiveness of the Project-Based Learning (PjBL) model in enhancing student engagement and learning outcomes in Informatics at a vocational high school. The research was motivated by the low initial understanding and passive learning behavior among students, which often leads to suboptimal academic achievement. The objective was to determine whether the PjBL approach could significantly improve both student activity and performance. A quasi-experimental design with a pretest-posttest control group was employed, involving 51 Grade X students from SMKN 1 Painan, divided into an experimental group (PjBL) and a control group (conventional teaching). Data were collected through tests, observations, and documentation, and analyzed using descriptive and inferential statistics. Results showed a significant increase in the experimental group’s posttest scores (mean = 78.04; N-Gain = 0.56) compared to the control group (mean = 64.56; N-Gain = 0.28). Student activity also improved across three meetings. Statistical tests confirmed the differences were significant (p < 0.05). These findings indicate that PjBL is more effective than traditional methods in promoting academic success and active learning in vocational education